Transient analysis of solar polygeneration systems including seawater desalination: A comparison between linear Fresnel and evacuated solar collectors. (1st April 2019) - Calise, Francesco; Dentice d'Accadia, Massimo; Vanoli, Raffaele; Vicidomini, Maria
Abstract: The paper presents a thermoeconomic comparison between two different solar thermal technologies, namely Linear Fresnel Reflector (LFR) and evacuated tube solar collectors (ETC), integrated into a polygeneration plant. The system produces space heating and cooling, domestic hot water and drinkable desalinated water, by means of a multi-effect distillation (MED) system. In the ETC layout, a single-effect LiBrH2 O absorption chiller (ACH) is included; in the second layout, based on LFR collectors, a double-effect ACH is considered. An auxiliary biomass-fired heater is used to supply the additional heat required by the MED unit, in case of low availability of solar radiation. Both plants are simulated by means of a zero-dimensional dynamic simulation energy model, developed in TRNSYS environment. The model also includes detailed thermo-economic calculations. The results show that in some winter weeks, the solar fraction for freshwater production ranges between 15% and 20% for the ETC-based system, whereas is zero in case of LFR, when the MED unit is supplied only by the biomass auxiliary heater. Therefore, for the analysed case study, ETCs resulted more profitable than LFRs, achieving simple pay-back periods of about 4–5 years. Highlights: The analysed polygeneration plant produces fresh water, heat and cool. Linear Fresnel and evacuated tubes solar collectors are compared. Solar desalination technique is based on multi-effect distillation process. The system is dynamically simulated in TRNSYS environment. Evacuated solar collectors achieve lower pay back periods equal to 3.52 years.